2020
DOI: 10.18203/2349-3291.ijcp20202159
|View full text |Cite
|
Sign up to set email alerts
|

Audit of transfusion practices in pediatrics in a tertiary care hospital

Abstract: Background: Audit of transfusion practices in pediatric patients was performed to study indications, clinical profile and whether transfusions were in accordance to guidelines.Methods: Retrospective analysis of all episodes of transfusions from a tertiary care centre was done. The study period was from January 2018 to December 2018.Patients in the age group of 4 months to 12 years were enrolled in the study. The data was reviewed according to the British Committee for Standards in Haematology guidelines for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Red cell concentrates are the most frequently transfused component in our study (55.7%), narrated similarly by Vaishnavi et al 14 in their study (66%) which also concluded red cell concentrates to be the most appropriately transfused component as well (64.8%). Our study highlighted a significant percent of fresh frozen plasma transfused inappropriately (54%) due to its use as a volume expander and also in the settings of normal coagulation tests, seen similarly in an audit conducted by Wade et al 15 Present study showed platelets to be the most inappropriately transfused component (57%).…”
Section: Discussionsupporting
confidence: 87%
“…Red cell concentrates are the most frequently transfused component in our study (55.7%), narrated similarly by Vaishnavi et al 14 in their study (66%) which also concluded red cell concentrates to be the most appropriately transfused component as well (64.8%). Our study highlighted a significant percent of fresh frozen plasma transfused inappropriately (54%) due to its use as a volume expander and also in the settings of normal coagulation tests, seen similarly in an audit conducted by Wade et al 15 Present study showed platelets to be the most inappropriately transfused component (57%).…”
Section: Discussionsupporting
confidence: 87%